2019
DOI: 10.1111/eva.12754
|View full text |Cite
|
Sign up to set email alerts
|

Population genomic analyses reveal a highly differentiated and endangered genetic cluster of northern goshawks (Accipiter gentilis laingi) in Haida Gwaii

Abstract: Accurate knowledge of geographic ranges and genetic relationships among populations is important when managing a species or population of conservation concern. Along the western coast of Canada, a subspecies of the northern goshawk ( Accipiter gentilis laingi ) is legally designated as Threatened. The range and distinctness of this form, in comparison with the broadly distributed North American subspecies ( Accipiter gentilis atricapillus ), is unclear. Given this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
(110 reference statements)
1
14
0
Order By: Relevance
“…Still, our inference of SC supports the hypothesis that smaller micro-refugia have persisted along the Pacific Coast [43,64]. In particular, the Haida Gwaii archipelago is known for high endemism, and its role as a refugium for mammals, invertebrates, and angiosperms is well established [64][65][66]. The divergence time inferred between populations from California and Haida Gwaii was relatively recent (39 KyA), in the range of inferred divergence times for bird species from the region [67] and in the time frame of the last interglacial period 55 to 25 KyA.…”
Section: Expansion From a Major Southern Refugium And Secondary Contasupporting
confidence: 84%
“…Still, our inference of SC supports the hypothesis that smaller micro-refugia have persisted along the Pacific Coast [43,64]. In particular, the Haida Gwaii archipelago is known for high endemism, and its role as a refugium for mammals, invertebrates, and angiosperms is well established [64][65][66]. The divergence time inferred between populations from California and Haida Gwaii was relatively recent (39 KyA), in the range of inferred divergence times for bird species from the region [67] and in the time frame of the last interglacial period 55 to 25 KyA.…”
Section: Expansion From a Major Southern Refugium And Secondary Contasupporting
confidence: 84%
“…2018), Bald Eagle Haliaeetus leucocephalu; F ST = 0.037-0.203 (Judkins et al . 2019), and Northern Goshawk Accipiter gentilis; F ST = 0-0.093 (Geraldes et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In statistical analysis, the recordings of the Palearctic gentilis-group, which comprise multiple subspecies, were treated as a single operational taxonomic unit (OTU) because there were no major subdivisions in a mitochondrial Control Region phylogeny (Kunz et al 2019). The Nearctic recordings represented three subspecies, A. g. atricapillus, A. g. laingi and A. g. apache, which were treated as a single OTU based on the results of Geraldes et al (2019) and Kunz et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…In an analysis of short mitochondrial COI sequences, Breman et al (2013) found that A. g. gentilis was more closely related to black sparrowhawk A. melanoleucus than to A. g. atricapillus but with very poor support. Using genomic DNA sequences, Geraldes et al (2019) found a deep divergence between Palearctic and Nearctic populations of A. gentilis. In a detailed mitochondrial DNA study, Kunz et al (2019) showed that Nearctic A. g. atricapillus, A. g. laingi and A. g. apache (hereafter atricapillus-group) and the Palearctic subspecies of A. gentilis (hereafter gentilis-group) formed reciprocally monophyletic groups which were not sister groups because the gentilis-group was closer to Meyer's goshawk A. meyerianus, Henst's goshawk A. henstii and A. melanoleucus than to the atricapillus-group.…”
Section: Introductionmentioning
confidence: 99%